Urban ecology in Latin America should be more interdisciplinary: Interview with Dr. Lucas M. Leveau (Terr@ Plural, 2019)
Interview with Dr. Lucas Matías Leveau, a Research Assistant and teacher of Community Ecology at the University of Buenos Aires, Argentina. He is interested in the biodiversity of human-modified environments, especially urban areas, and crops, and is currently fellow of CONICET (Consejo Nacional de Investigaciones Científicas y Técnicas). He is interested mainly in factors that mold bird communities and bird behavior in urban areas based on multiple spatial and temporal scales. Dr. Leveau uses several approach types, such as field observation, international collaborative work, and meta-analysis Dr. Leveau compounds the Editorial Board of the Journal of Urban Ecology.